Fiscal decentralization and local government size in Chinese prefecture-level cities: does fiscal transparency matter? - Liu, Cong; Abd Ghani, Judhiana; Bui Kher Thinng, Wency (Babes-Bolyai University, 2025)
Fiscal transparency strengthens accountability mechanisms through mitigating information asymmetry, probably moderating the effect of fiscal decentralization on local government size. Using data from 283 Chinese prefecture-level cities, this study tests the hypothesis with the Generalized Method of Moments (GMM) estimator. We find that fiscal decentralization expands local government size under low transparency, but this positive effect weakens as transparency improves and becomes insignificant beyond a threshold. Vertical balance, reflecting reliance on own-source revenue, initially increases government size, but this effect diminishes with higher fiscal transparency and turns negative at higher transparency levels. These findings reveal that the common-pool hypothesis holds conditionally, suggesting that fiscal transparency is critical to ensure that fiscal decentralization promotes efficient public resource allocation.